MA ELT Quick Fire Presentation event 2022 at University of Warwick: a reflective report / Alyssa Batrisyia Zainal Abidin - Zainal Abidin, Alyssa Batrisyia (Academy of Language Studies, 2023)
The Master of Arts (MA) English Language Teaching (ELT) Quick Fire Event Presentation is held annually by the Applied Linguistics Department at the University of Warwick, with support from the International Association of Teachers of English (IATEFL) Research Special Interest Group (Research SIG). The event aims to create a space for MA students from UK universities to share the preliminary findings of their dissertations with others. At last year's event in August, each presenter delivered a quick 5-minute presentation about their dissertation, followed by 5 minutes of breakout discussion and 10 minutes of Q and A. At that time, I was doing my MA TESOL Pre-Service at University College London and joined the event as an observer whilst supporting my peers in participating in the event. The event had a diverse range of ELT topics from investigating argumentative tasks such as debates on L2 speech production and aptitude (Mari Ito from University College London) to exploring Foreign Language Anxiety (FLA) amongst adult migrants (refugees, asylum seekers, and forced migrants) in an ESOL/EFL class in Scotland (Mathilde Smith from the University of Strathclyde).